Eksperimentasi Visual: Ekspresi Pergerakan Kaki Yang Bergelang Salangai Dalam Tarian Bharata Natyam - Thiviya, A/P Arumugam (Universiti Malaysia Sarawak(SARAWAK), 2018)
This study was conducted to observe the visual expression derived from the movement of the feet wearing Salangai in Bharata Natyam dance. The researcher identifies various types of feet movements that portrays expressive element in the dance. The visual expression of the feet movements in the dance was analysed for adaption in the form of contemporary works. The researcher employed a qualitative approach in the form of reference, observation and experimentation to acquire substantial data collection. The researcher emphasizes the visual expression through the stomping of the feet onto the surface filled with kolam powder. The expression was further enhanced by the harmonious ringings of the bell from the anklet. It is hoped that this study could provide a new experience to the audience to see the expression from movement of the feet in traditional dance